2022
DOI: 10.3390/plants11192486
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacillus velezensis RDA1 as a Biological Control Agent against White Root Rot Disease Caused by Rosellinia necatrix

Abstract: White root rot disease, caused by Rosellinia necatrix, poses a threat to several tree crops; hence, effective and sustainable strategies to control this disease remain warranted. This study identified an effective R. necatrix biocontrol agent by isolating 32 strains from soil samples collected from white root rot-infested organic pear orchards, among which RDA1 exhibited the most potent growth-inhibitory effects. Microbiological and 16S rRNA gene sequencing analyses revealed that the bacterial isolate belonged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…B. subtilis Bs 8B-1 has produced a sufficient amount of antifungal VOCs after 5 days of incubation with Phytophthora capsici , causing cucumber damping-off, and Rhizoctonia solani , causing radish damping-off [ 45 ]. B. velezensis RDA1 VOCs inhibited the growth of Rosellinia necatrix by approximately 60–70% compared to control after 10 days of treatment [ 46 ].…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%
“…B. subtilis Bs 8B-1 has produced a sufficient amount of antifungal VOCs after 5 days of incubation with Phytophthora capsici , causing cucumber damping-off, and Rhizoctonia solani , causing radish damping-off [ 45 ]. B. velezensis RDA1 VOCs inhibited the growth of Rosellinia necatrix by approximately 60–70% compared to control after 10 days of treatment [ 46 ].…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%
“…As B. velezensis UTB96 has superior lipopeptide production, it was reasonable to observe enhanced antifungal activity against D. longicolla compared to FZB42 (Figure 4). Previous studies have demonstrated that Bacillus velezensis strains have a broad antagonism activity against several fungal phytopathogens such as soil-borne pathogens Fusarium graminearum, F. solani, F. oxysporum, Rhizoctonia solani, Ralstonia solanacearum, Rosellinia necatrix [55][56][57][58] and the common postharvest pathogens like Botrytis cinerea, Penicillium digitatum and Monilinia fructicola [59][60][61]. More specifically, it is reported that the lipopeptides bacillomycin D and fengycin produced by FZB42 contribute significantly to antifungal activity [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…For example, strains of B subtilis, which are abundant in the environment, produce antibiotic lipopeptides, including iturin [74], surfactants [75], and fengycin [76]. Enzymes of the lipopeptide group protect Fusarium oxysporum [75], and Rosellinia necatrix in horticultural crops [78], by inducing systemic resistance in the host plant or suppressing the growth of pathogenic fungi directly [79][80][81]. This shows the potential use of indigenous Bacillus as a plant regulator and biocontrol of potato pathogens.…”
Section: (C))mentioning
confidence: 99%